Enterprise Risk Management Effectiveness: Role of Job Embeddedness, Change Management Awareness and Ethical Climate - Hashed Mabkhot; Sanjar Mirzaliev (Decision Making: Applications in Management and Engineering, 2025)
This study examines the impact of job embeddedness and change management awareness on enterprise risk management (ERM) effectiveness. It also explores the mediating role of change management awareness and the moderating role of ethical climate in these relationships. Additionally, the study investigates industry differences between the service and production sectors using a multi-group analysis (MGA). A quantitative research design was adopted, collecting data from 236 respondents, 143 from the service industry and 93 from the production industry. Respondents were mid-to-senior level employees involved in risk management and organizational decision-making. A structured questionnaire using validated scales was administered, and data were analyzed using Smart-PLS 4.0 for PLS-SEM and multi-group analysis. The results indicate that awareness of change management and job embeddedness have a significant and positive effect on the effectiveness of ERM. Ethical environment, while moderating the relationships between work embeddedness and ERM effectiveness and change management awareness, mediates the relationship between job embeddedness and ERM effectiveness. The MGA results indicated substantial industry variations. Job embeddedness is particularly important in manufacturing, whereas knowledge of change management is more crucial to ERM success in services. This study contributes to ERM literature by integrating job embeddedness and change management awareness into risk management frameworks. It also highlights the role of ethical climate and industry differences, offering theoretical and practical insights for organizations aiming to enhance ERM effectiveness